Foot orthoses based on bombyx silk fiber polymer composite in the treatment of flexible flat feet children - Suwicha Techapoowapat (Prince of Songkla University, 2014)
Thesis (M.Sc., Biomedical Engineering)--Prince of Songkla University, 2013